Cranial dermoid cyst with long-term development treated by ethanol sclerotherapy: a case report. Issue 1 (1st January 2020) - Kitazawa, Takeshi; Shiba, Masato; Nagaya, Hiroyuki; Yuzuriha, Shunsuke
Abstract: Here, we describe the case of an 80-year-old woman who presented with cranial dermoid cyst causing orbital disfigurement. The cyst was treated successfully with ethanol sclerotherapy and has shown no growth for 1 year.